SOCIAL HEROES PROJECT: EDUKASI MAHASISWA TENTANG RISIKO JATUH KEPADA LANSIA - Azzahra, Gading Nasywa Aji; Maulina, Rufidah; Azzahra, Nabila Khairunisa (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2022)
Background: The elderly is a condition where there are many physical and psychosocial changes, one of which is the risk of falling. The risk of falling in the elderly can be anticipated by conducting education or counseling so that awareness in the elderly will increase. The purpose of this community service is to provide information to the elderly and provide assistance. Method: This service involves 27 student committees, 8 volunteers, and 16 elderly at the Wreda Dharma Bakti Orphanage, Surakarta on June 25, 2022. The activities carried out are counseling on the risk of falling, thrashing and sewing activities, entertainment, and distribution of aid. Results: Community service activities went smoothly, the elderly seemed enthusiastic in participating in the activities indicated by the good therapeutic relationship between the two parties. The benefits are also felt by the organizers to explore the role of the profession as health workers. Conclusion: Counseling about the risk of falling can increase awareness about the risk of falling on him. Counseling activities can involve facilitators or nursing home staff in order to anticipate the risk of falling to the elderly in their nursing homes. Keywords: Elderly, Extension,Risk of Falling